Spatiotemporal characteristics of swallowing in Parkinson's disease. (5th August 2014) - Kim, Yeo H.; Oh, Byung‐Mo; Jung, II‐Young; Lee, Jung C.; Lee, Goo J.; Han, Tai R.
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis The aim of this study was to quantitatively investigate spatiotemporal movement abnormalities during the pharyngeal phase of swallowing in individuals with Parkinson's disease (PD) and to investigate relationships between disease and dysphagia severities. Study Design Retrospective study. Methods We performed two‐dimensional motion analysis of the hyoid bone, epiglottis, and vocal folds using videofluoroscopic images from 33 PD patients and 33 age‐matched, healthy controls. The outcome measures were spatial and temporal movement variables during swallowing. Additionally, three subgroups of patients were compared based on the Hoehn and Yahr scale to identify the relationship between disease and dysphagia severities. Results Individuals with PD showed a reduced anterior hyoid bone displacement after normalization for each individual. The maximal angle of the epiglottic rotation was smaller in PD patients. The time to maximal displacement of the hyoid bone, epiglottis, and vocal folds were significantly delayed in PD patients (P = 0.001, 0.002, and < 0.001, respectively); the mean velocities of the hyoid bone and epiglottic movements were also reduced in PD patients (P < 0.001 and < 0.001, respectively). The velocity curves of the hyoid bone revealed more peaks in individuals with PD, representing incoordination during swallowing. Clinical disease severity was related to level of diet and supervision but not with dysphagia severity. Conclusion This study shows that oropharyngeal bradykinesia, incoordination, reduced anterior hyoid bone movement, and decreased epiglottic rotation angle during swallowing are the most noticeable findings in individuals with PD. Level of Evidence N/A. Laryngoscope, 125:389–395, 2015